A Patient with AIDS and Embolic Stroke: A Case Report - Troy Fonda; Usman Hadi (Institute of Medico-legal Publications Pvt Ltd, 2021)
Human immunodeficiency virus (HIV) infection is a global concern. Globally, 36.7 million people areliving with HIV and 1 million people died at the end of 2016. There is an association between humanimmunodeficiency virus (HIV) infection with neurological manifestations. Between 1% and 5% of patientswith HIV develop stroke. The pathogenesis of AIDS with stroke is still controversial. A 37-year-old malepatient with AIDS had an embolic stroke. The diagnosis of the patient was based on clinical condition andthe CT scan results of the head with contrast. The stroke-causing mechanism in patients is HIV-associatedvasculopathy that results from accelerated atherosclerosis. After administration of antiplatelet and statin, thepatient’s condition improves.